PERSPEKTIF BALANCED SCORE-CARD DALAM PENGUKURAN PRODUKTIVITAS ORGANISASI - Rachmad Hidayat (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2008)
Balanced Scorecard system may affect the company’s productivity in the forms of financial perspective, internal business process perspective, and learning as well as growth perspective. A manager shall consider its benefits before implementic the system to the company. This research uses quantitative data obtained from accounting and producting staffs. Data are analyzd by using statistical experiment as the analysis tool to test the hypothesi using F test to find out the correlation of research variable simultaneously, and t-test to find out the relationship of multiple linear regression of equality partialy. And the result is that there is correlation between company’s productivity and perspectives in Balanced Scorecard. The dominant effect toward the company’s productivity is learning and growth perspective and internal business process perspective.